Group versus individual treatment for substance use disorders: a study protocol for the COMDAT trial - Sidsel Helena Karsberg; Mads Uffe Pedersen; Morten Hesse; Birgitte Thylstrup; Michael Mulbjerg Pedersen (BMC, 2021)
Abstract Background Alcohol and other drug use disorders contribute substantially to the global burden of illness. The majority of people with substance use disorders do not receive any treatment for their problems, and developing treatments that are attractive and effective to patients should be a priority. However, whether treatment is best delivered in a group format or an individual format has only been studied to a very limited degree. The COMDAT (Combined Drug and Alcohol Treatment) trial evaluates the feasibility, acceptability, and cost effectiveness of MOVE group (MOVE-G) treatment versus MOVE individual (MOVE-I) treatment in four community-based outpatient treatment centres in Denmark. Methods A two-arm non-inferiority trial comparing MOVE-I (Pedersen et al., Drug Alcohol Depend 218:108363, 2020) with MOVE-G a combined group treatment for both alcohol use disorder and drug use disorder. The primary objective is to examine whether MOVE-G is non-inferior to MOVE-I in relation to abstinence from drug and/or alcohol, number of sessions received, and completion of treatment as planned. All participants will receive treatment based on cognitive behavioral therapy and motivational interviewing, vouchers for attendance and text reminders, as well as medication as needed (MOVE). Participants (n = 300) will be recruited over a one-year period at four public treatment centers in four Danish municipalities. A short screening will determine eligibility and randomization status. Hereafter, participants will be randomized to the two treatment arms. A thorough baseline assessment will be conducted approximately 1 week after randomization. Follow-up assessments will be conducted at 9 months post-randomization. In addition, patients' use of drugs and alcohol, and patients' wellbeing will be measured in all sessions. The main outcome measures are drug and alcohol intake at 9 months follow-up, number of sessions attended, and dropout from treatment. Discussion The present study will examine the potential and efficacy of combined groups (patients with alcohol and drug disorders in the same group) versus individually based treatment both based on the treatment method MOVE (Pedersen et al., Drug Alcohol Depend 218:108363, 2020). Trial registration ISRCTN88025085 , registration date 30/06/2020.